A comparative study of educational placement and school adjustment of children with cochlear implants between China and Czech Republic. (August 2019) - Wu, Jiaojiao; Liu, Shenglin
Abstract: To investigate and compare educational placement and school adjustment of children with cochlear implants between China and Czech Republic for more appropriate educational placement, and facilitating school adjustment. This comparative study of 43 children with cochlear implants between Czech and China was conducted through questionnaire survey and in-depth interview followed by field observation. Among a continuum of educational placement including regular class, resource room, deaf school, institution and home stay, research findings suggest participant children generally adapt to the placement based on three indicators: environmental conditions, interpersonal relationship and academic achievement. Statistically significant difference exists in overall school adjustment of children between the groups. Child characteristics, family related and placement related factors influence on both of educational placement and school adjustment. Educational support provided in regular school is inadequate. Reported by both groups that communication barrier and poor academic performance are main reasons for children's transition from regular class to deaf school.